QRS Detection On Heart Rate Variability Readings using Two Moving Average Methods - Ayu Nissa Berlianri Rizhky; I Dewa Gede Hari Wisana; Sima Das (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
Heart Rate Variability or heart rate in humans is used to unify the heart rate in humans, the function of the heart rate monitor is used to unite the human heart rate. The purpose of making this tool is to read the human heart rate using the Two Moving Average method or moving average which makes it easy to find the R peak to peak signal, making it easier to read. This is achieved by discovering and studying each window size change specified by, so that it can be seen the change in every two moving averages for each window size value. This study uses the Arduino Nano system for data processing and uses Delphi to display the processed data. In this study examined signaling and heart rate monitoring for 5 minutes. In this study it can be said that, the best window size with the best signal results for measuring heart rate is the window size 15 . this method is a method with a good accuracy rate of 98%. And also this method can be displayed directly by displaying the RR Interval and HRV value for 10 minutes with results close to 0. This method is recommended to detect high enough P and T signal.